Manganese–methionine chelate improves antioxidant activity, immune system and egg manganese enrichment in the aged laying hens. Issue 1 (21st November 2022) - Khoshbin, Mohammad Reza; Vakili, Reza; Tahmasbi, Abdol‐Mansour
Abstract: Background: It has been reported that supplementation of manganese (Mn) could alleviate the negative effects of age on egg quality in laying hens. However, limited information is available on compensatory ways in order to reduce the adverse effects of hen age on health and Mn deposition in the body. Objectives: The objectives were to investigate the effect of organic and inorganic sources of Mn on antioxidant activity, immune system, liver enzymes, shell quality and Mn deposition in the tissues of older laying hens. Methods: A total of 250, 80‐week‐old Leghorn laying hens (w36) were allocated into five treatment groups with five replications in a completely randomised design. Treatments were control (without Mn supplementation), 100% Mn sulphate, 75% Mn sulphate + 25% organic Mn chelate, 50% Mn sulphate + 50% organic Mn chelate and 25% Mn sulphate + 75% organic Mn chelate. Results: The groups fed 50 and 75% organic Mn chelate exhibited the lowest feed conversion ratio, as well as the maximum laying percentage, and egg weight and mass. Except to those fed 75% Mn sulphate, the hens received Mn supplements either as organic or inorganic, had higher immunoglobulin G and M compared with the control ( p  < 0.05). A significant elevation in the values of superoxide dismutase was observed in the hens receiving 50 and 75% organic Mn chelate when compared with the other treatments. The ALP activity decreased with increasing organic Mn chelate. Mn supplementation, either as organic or inorganic, increased Mn deposition in bone, egg yolk and shell, serum and liver. Conclusion: Dietary supplementation with 50–75% Mn–methionine has the potential to replace Mn‐sulphate in laying hens' diet for improving eggshell quality, Mn deposition in the eggshell, antioxidant capacity and immune response, as well as improving laying performance, egg weight and feed conversion ratio. Abstract : Dietary supplementation with 50–75% Mn–methionine has the potential to replace Mn‐sulphate in laying hens' diet for improving eggshell quality, Mn deposition in the eggshell, antioxidant capacity and immune response, as well as improving laying performance, egg weight and feed conversion ratio